Catalytic Hydrophosphination of Isocyanates by Molecular Antimony Phosphanides. Issue 13 (24th March 2022) - Schwamm, Ryan J.; Coles, Martyn P.
Abstract: The terminal antimony phosphanides Sb(NON Dipp )(PR2 ) (NON Dipp =[O(SiMe2 NDipp)2 ] 2− ; Dipp=2, 6‐ i Pr2 C6 H3 ; R=Cy, Ph) were assessed for catalytic hydrophosphination reactivity. Stoichiometric reactions showed that phenylisocyanate inserts into the Sb−P bond to afford the phosphanylcarboxamidate complex, and subsequent reaction with Cy2 P−H confirmed liberation of Cy2 PC(O)NHPh. Catalytic hydrophosphination of PhN=C=O by Ph2 P−H was demonstrated using 1 mol % catalyst at room temperature. A mixture of mono‐ and di‐insertion products were produced under these conditions. Abstract : The hydrophosphination of phenylisocyanate with Ph2 P−H is catalysed by the terminal antimony phosphanide compound Sb(NON Dipp )(PPh2 ), producing a mixture of mono‐ and di‐insertion products. Stoichiometric reactions with the dicyclophosphanido analogue confirm insertion of PhN=C=O into the Sb−P bond to afford the phosphanylcarboxamidate complex.